Reaching High: Occupational Sorting and Higher Education Wage Inequality in the UK - Jan Kleibrink; Maren M. Michaelsen (Institute for the Study of Labor (IZA), 2014)
The Further and Higher Education Act of 1992 changed the Higher Education system in the UK by giving all polytechnics university status. Using the British Household Panel Survey and accounting for different sources of selection bias, we show that wage differentials between university and polytechnic graduates can be explained by a glass ceiling preventing polytechnic graduates from reaching professional occupations. After the reform, the glass ceiling disappeared and average wages of post-reform polytechnic graduates are not statistically different from average wages of post-reform graduates of traditional universities any more. This implies that the abolition of the 'two-tier' education system has reduced inequality among Higher Education graduates a result that may be desirable in other systems of a 'two-tier' nature.
Keywords: I23; J31; J64; 330; higher education; education reform; wage differentials; occupational sorting; United Kingdom